Isolation of Bacteria Causing Secondary Bacterial Infection In TheDry l ,esions Of Cutaneous Leishmaniasis - S. Al-Bayati, Abdullah; M. Al-juboori, Osama; A. Ahmed, Ahmed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Abstract Cutaneous loishrnaniasts (CL) is a parasitic disease characterized by single or multiple lesions,. Sc ontlay bacterial infection is one of the complications of the Jiscase that Can increase the titute destruction and the resultant sear. To determine effectively the u3cidence of real tamaindary bacterial infection in the dry type, of cutaneous leishmaniasis ,we designed the current study. This was a crusts-sectional study performed in the outpatient clinic of dermatology and vencriology nt Unit Teaching Hospital. A total of 37 patients with etinica3 diagnosis of Cutaneous leishmaniasis (dry type) were, carolled in this study. Samples were taken from all patients. The skin areas surrounding the lesions were thoroughly cleaned using cotton wool moistened with alcoholic iodine. After appropriate cleaning, the samples were collected aseptically by scraping of sterile swabs of the lesions All the samples were transferred uo Mac Cunkeys agar and blood agar_ After 24 hours incubation (aerobically& en aerobically) at 37 tIC, the species atilt bacteria were determined. Then site samples were transferred to Mueller-Hinton agar or nutrient agar for sensitivity test. After 24 hours incubation at 37 °C, the diameters of the inhibition zones were measured to determined the sensitivity Among the 37 patients with Cutaneous leislununiasis the results of the culture were positive in 12 patients (32.4%). 11 of them (91.6%) have more than one lesion and 9 patients (75%) of them were less than 5 years old. and 3 patients (25%) were more than 5 years old_ Bacteria isolated from the lesions were Staph. aureus in II patients (91.6%)( and all were sensitive to Rifampicin) and E.Coli in one patient (LI%) which was sensitive to Amikacin & Norlioxacini The incidence of secondary bacterial infection with a dry type of Cl., was (32.4%), (91.6%) of them had multiple lesions, and (75%) were less than 5 years old, The most common bacterial isolate was Staphylouocus ttureus